An analysis of the role of security service in promoting peace, security and development in Zimbabwe: a case study of Zimbabwe Prison and Correctional Services (ZPCS). - Makotore, Anotida (Midlands State University, 2019)
Zimbabwe Prison and Correctional Services (ZPCS) cannot afford to adequate resources for prisoners from various prison centers. These centers are Chikurubi Maximum Prison, Mutimurefu Prison, Mutare Prison, Harare Central Prison and Whawha Medium Prison. Prisoners are facing challenges to access health facilities and good hygiene, transport, food, clothes and other basic items which they may need for example sanitary pads for women . Juveniles lack stationary to upgrade themselves in their educational studies and they are also in need of sport kits such as those for tennis, netballs, footballs and volleyballs. However prisoners and prison officers they face a quite number of challenges for example lack machinery to use in their farming activities such shortages would lead prison service into a forum of punishment. This research analyses the role of the security service in promoting peace, security and development in Zimbabwe. ZPCS rehabilitates and reintegrate prisoners through a number of programs and activities such as workshops, bands, dramas and cancelling sessions. Mediating between inmates and their relatives and friends to heal and comfort prisoners where as there is need to conciliate with friends and relatives. The research also patterns prisoner’s protection, in cooperated into all national capacities in peace, security and development through giving them dignity and should be represented where necessary for the humanitarian assistance and human rights action by the government, non-governmental organization, civil societies for example churches, independent bodies and commissions. There should be improved work of service by ZPCS in handling inmates with a broad research and assistance from various institutions such as ZACRO and ICRC. The study provides alternative choices in decision making which the ZPCS could rely on in its daily service by avoiding victimizing prisoners and should allow them to participate in their area of interest and specialization to promote peace, security and development locally, regionally and internationally.